Engineering Efficient p‐Type TMD/Metal Contacts Using Fluorographene as a Buffer Layer. (26th April 2017) - Musso, Tiziana; Kumar, Priyank V.; Grossman, Jeffrey C.; Foster, Adam S.
Abstract : P‐type transistors based on high work function transition metal dichalcogenide (TMD) monolayers such as MoS2 are to date difficult to produce, owing to the strong Fermi level pinning at the semiconductor/contact metal interfaces. In this work, the potential of halogenated graphenes is demonstrated as a new class of efficient hole injection layers to TMDs such as MoS2 and WSe2 by taking fluorographene (or GF) as a model buffer layer. Using first‐principles computations, two commonly obtained GF stoichiometries, C2 F and CF, have been studied as buffer layers between MoS2 and Pt. In particular, for high work function TMDs such as MoS2, it has been shown that C2 F forms an ohmic contact, while CF leads to a significant p‐SBH value. On the other hand, for low work function TMDs such as WSe2, both C2 F and CF lead to p‐type ohmic contacts. This analysis shows that the ability of these buffer layers to form p‐type contacts depends crucially on the charge redistribution at the GF/metal interface, which is dictated by their chemical interaction and equilibrium geometry. The fundamental electronic structures between the different semiconductor/insulator/metal interfaces which are part of this study have also been investigated. Abstract : Metal/graphene fluoride/transition metal dichalcogenide (TMD) interfaces are investigated through ab initio methods for two GF stoichiometries, C2 F and CF. In its C2 F form, graphene fluoride is shown to be an efficient hole‐injection layer, resulting in ohmic contacts to MoS2 . The use of graphene fluoride allows the fabrication of efficient TMD‐based p‐type electronic devices.